2016
DOI: 10.1016/j.mod.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of planar cell polarity protein Vangl2 in the mouse oviduct epithelium

Abstract: The planar cell polarity (PCP) pathway regulates morphogenesis in various organs. The polarized localization is a key feature of core PCP factors for orchestrating cell polarity in an epithelial sheet. Several studies using Drosophila melanogaster have investigated the mechanism of the polarized localization. However, to what extent these mechanisms are conserved and how the polarization of core PCP factors is maintained in mature vertebrates are still open questions. Here, we addressed these questions by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…Interestingly, while polarized microtubules are essential for establishing some PCP asymmetries, they may be dispensable for maintaining these patterns once they have been stably generated 37,40 , and this supports the notion that the key role of microtubules in PCP patterning is to introduce an initial directional bias. It has separately been shown that intact PCP patterns are necessary for the polarization of microtubule arrays 24,38,41 , demonstrating that intricate and mutual relationships exist between microtubule polarity and planar polarity patterning.…”
Section: Establishment Of Core Pcp Patternssupporting
confidence: 62%
See 2 more Smart Citations
“…Interestingly, while polarized microtubules are essential for establishing some PCP asymmetries, they may be dispensable for maintaining these patterns once they have been stably generated 37,40 , and this supports the notion that the key role of microtubules in PCP patterning is to introduce an initial directional bias. It has separately been shown that intact PCP patterns are necessary for the polarization of microtubule arrays 24,38,41 , demonstrating that intricate and mutual relationships exist between microtubule polarity and planar polarity patterning.…”
Section: Establishment Of Core Pcp Patternssupporting
confidence: 62%
“…Directional beating of MCCs has been studied on the amphibian epidermis for nearly 200 years 86 , and not surprisingly, the first description of a role for PCP genes in these cells was in this context 63,87 . PCP signalling is now known to control polarized beating in all MCCs examined to date, including in the mammalian brain 64,8890 , airway 24 , and oviduct 40,91 . Core PCP localization examined in these tissues reflects that seen in the fly wing; PK and VANGL occupy a domain complementary to that of DVL and FZ (Fig.…”
Section: From Molecular To Functional Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Celsr1, Vangl2, and Fzd3 are similarly accumulated asymmetrically in the apical compartment of RGCs and E1 cells, next to the intercellular junctions (Fig. 1)[13, 15, 56, 58, 71]. Ablation of Vangl2 or Fzd3 affects the establishments of both rotational and translational polarity in E1 cells [13, 14, 56].…”
Section: Regulation Of E1 Cells’ Pcp By Pcp Regulatorsmentioning
confidence: 99%
“…Over the last decade growing evidence has linked the planar cell polarity (PCP) pathway as a signaling system to regulate polarized ciliary localizations. PCP has been shown to be critical for proper positioning and orientation of cilia in multiciliated cells in the Xenopus larval skin [3739], ependymal cells in mice [40], and epithelial cells in the oviduct [41, 42]. Similarly, primary cilia positioning is regulated by PCP in the mouse node [43], the outer hair cells in the mouse cochlea [30, 31], the floor plate from zebrafish [22], cell lens in mice [44], and planaria [45].…”
Section: Do Centrioles Move In Epithelial Cells?mentioning
confidence: 99%